IEEE Antennas and Propagation Society International Symposium. 2001 Digest. Held in Conjunction With: USNC/URSI National Radio
DOI: 10.1109/aps.2001.959494
|View full text |Cite
|
Sign up to set email alerts
|

Design of an efficient miniaturized UHF planar antenna

Abstract: In this paper, the design aspects and the measured results of a novel miniaturized planar antenna are described. Such architectural antenna design is of great importance in mobile military communications where low visibility and high mobility are required. Slot radiating elements, having a planar geometry and capable of transmitting vertical polarization when placed nearly horizontal, are appropriate for the applications at hand. Slot antennas also have another useful property, so far as impedance matching is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
0

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 7 publications
0
23
0
Order By: Relevance
“…Incidentally (according to them), the width w of an impedance sections has only a small effect on the scattering parameters in comparison with the length l, where the height h of the sections is oriented transversely to the current flow. Of particular interest therefore is the definition of Hong where he defined quasi-lumped element as microstrip line short sections and stubs whose physical lengths are smaller than a quarter of guided wavelength at which they operate, and as such, are common components for approximate microwave realization of lumped elements in microstrip filters structures, and are termed quasi-lumped elements [2]. It is on the basis of this definition that the proposed derives its lumped element equivalency.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Incidentally (according to them), the width w of an impedance sections has only a small effect on the scattering parameters in comparison with the length l, where the height h of the sections is oriented transversely to the current flow. Of particular interest therefore is the definition of Hong where he defined quasi-lumped element as microstrip line short sections and stubs whose physical lengths are smaller than a quarter of guided wavelength at which they operate, and as such, are common components for approximate microwave realization of lumped elements in microstrip filters structures, and are termed quasi-lumped elements [2]. It is on the basis of this definition that the proposed derives its lumped element equivalency.…”
Section: Introductionmentioning
confidence: 99%
“…These works, though efficient suffer significant large antenna size. However, in [2], the authors reported the design of an efficient miniaturized UHF planar antenna employing spiral slot radiating elements. This work is noteworthy and adequate for UHF applications but suffer serious disadvantage most especially at high frequencies range of applications as it becomes unrealizable due to etching limitations.…”
Section: Introductionmentioning
confidence: 99%
“…Its electrical size can be reduced by the terminal loading method, such as antennas with H-shaped or spiral lines loading slots [19,20]. However, the slot antenna has a bi-directional pattern and is not suitable for many applications that require unidirectional radiation patterns.…”
Section: Introductionmentioning
confidence: 99%
“…Using meander, zigzag or spiral shapes can also reduce the antennas as they increase the electrical length of the antenna in a small area. Up to λ/10 antenna is designed using these shapes [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…This results in a demand for similar reductions in antenna size. Therefore researchers investigated different methods for miniaturization of the microstrip antenna [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%